Aldehyde dehydrogenase 6 family member A1 negatively regulates cell growth and to cisplatin sensitivity in bladder cancer. Issue 7 (26th April 2022) - Guo, Qi; Zhang, Tao; Gong, Yuwen; Tao, Yan; Gao, Yanjun; Wang, Yuhan; Tian, Junqiang; Zhang, Su; Wang, Hanzhang; Rodriguez, Ronald; Wang, Zhiping
Abstract: Aldehyde dehydrogenase 6 family member A1 (ALDH6A1) is a highly conserved member of aldehyde dehydrogenase (ALDHs) family. Recent studies reveal that it broadly involved in tumorigenesis and drug metabolism in kinds of cancer. However, the critical role of ALDH6A1 in bladder cancer progression and cisplatin resistance of cancer cells are still poorly understood. In this study, we researched the significant function of ALDH6A1 in bladder cancer. Our results showed that ALDH6A1 exhibited a decreased expression in clinical bladder cancer tissues and bladder cancer cell lines. Stable ALDH6A1 knockdown not only could promote cell growth and colony formation in bladder cancer cells, but also enhance drug resistance to cisplatin treatment. On the contrary, we found the active transcript factor hepatocyte nuclear factor 4α (HNF4α, NR2A1) by alveriene could upregulate ALDH6A1 expression, significantly inhibit the cell growth and colony formation of bladder cancer cells, and improve cisplatin sensitivity of bladder cancer cells. Together, our results show that ALDH6A1 plays as a tumor suppressor in bladder cancer, which regulated by HNF4a. ALDH6A1 could be a promising diagnostic marker and treatment target in bladder cancer.